Spondyloepiphyseal Dysplasia Tarda and Osteoporosis: A Case Report - Case Report - Şükran Kurtulmuş; Korhan Barış Bayram; Hikmet Koçyiğit; Sevtap Köksal Avcı; Yasemin Dinçer Turan; Alev Gürgan (Galenos Yayinevi, 2006)
Spondyloepiphyseal dysplasia (SED) tarda is a rare disease of which symptoms begin at childhood. It causes shortness of body and extremities, and kyphoscoliosis deformation due to delayed formation of epiphyses. Coexistence of osteopenia and the different types of this disease is also reported. According to our knowledge, the patient having both SED tarda and osteoporosis cured with the antiresorptive agents as well as his follow-up data are presented for the first time in the literature. (Osteoporoz Dünyasından 2006; 12 (1): 18-21)